The economics of art museums - Feldstein, Martin S. (Conference report (National Bureau of Economic Research), 1991)
The National Bureau of Economic Research organized a project to explore the economic issues facing the major art museums of the United States. For this purpose NBER defined economics broadly to include not only the financial situation of the museums but also the management and growth of museum collections, the museums' relationship with the public, and the role of the government in supporting art museums. This volume brings together nontechnical essays on these issues by economists associated with the NBER and personal statements by leaders of America's major national art muse.